Associative Study on Government Spending, Inflation, Trade Balance, and Gross Domestic Product - Agus Eko Sujianto; Muhammad Fajar Ulil Azmi (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2020)
Specifically, this study aims to examine the effect of macroeconomic indicators namely government spending, inflation and trade balance on PDB. The observation period from 1981-2017 is based on International Monetary Fund (IMF) documentation. Data analysis using the Error Correction Model (ECM). The results of the study: (1) in the short term and long term government spending significantly influence PDB; (2) in the short-run and long-run inflation affects PDB in the opposite way; (3) in the short term PDB is not affected by the trade balance, whereas in the long run the trade balance variable also has no effect on PDB with a negative slope and (4) the results of simultaneous tests of government expenditure, inflation, and the trade balance affect PDB.